Mechanisms of Comorbidities Associated With the Metabolic Syndrome: Insights from the JCR:LA-cp Corpulent Rat Strain - Diane, Abdoulaye; Pierce, W. David; Kelly, Sandra E.; Sokolik, Sharon; Borthwick, Faye; Jacome-Sosa, Miriam; Mangat, Rabban; Pradillo, Jesus Miguel; Allan, Stuart McRae; Ruth, Megan R.; Field, Catherine J.; Hutcheson, Rebecca; et al. (Frontiers in Nutrition, 2016)
Obesity and its metabolic complications have emerged as the epidemic of the new millennia. The use of obese rodent models continues to be a productive component of efforts to understand the concomitant metabolic complications of this disease. In 1978, the JCR:LA-cp rat model was developed with an autosomal recessive corpulent (cp) trait resulting from a premature stop codon in the extracellular domain of the leptin receptor. Rats that are heterozygous for the cp trait are lean-prone, while those that are homozygous (cp/cp) spontaneously display the pathophysiology of obesity as well as a metabolic syndrome-like phenotype. Over the years, there have been formidable scientific contributions that have originated from this rat model, much of which has been reviewed extensively up to 2008. The premise of these earlier studies focused on characterizing the pathophysiology of metabolic syndrome-like phenotype that was spontaneously apparent in this model. The purpose of this review is to highlight areas of recent advancement made possible by this model including; emerging appreciation of the ‘thrifty gene’ hypothesis in the context of obesity, the concept of how chronic inflammation may drive obesogenesis, the impact of acute forms of inflammation to the brain and periphery during chronic obesity, the role of dysfunctional insulin metabolism on lipid metabolism and vascular damage, the mechanistic basis for altered vascular function as well as novel parallels between the human condition and the female JCR:LA-cp rat as a model for polycystic ovary disease (PCOS).